Linkages Between Land Tenure Rights And Land Reform Processes - G.M.Mirzakarimova (Zien Journals, 2023)
Rights and Restrictions on Land Use The value of a property depends in part on what can be done with it. Land use rights and restrictions strongly influence the behavior of the land market and are one of the important factors that determine the value of real estate.
Keywords: rights; restriction; real estate; information